2017
DOI: 10.1111/een.12455
|View full text |Cite
|
Sign up to set email alerts
|

Response of Brassica oleracea to temporal variation in attack by two herbivores affects preference and performance of a third herbivore

Abstract: 1. Plants are frequently under attack by multiple insect herbivores, which may interact indirectly through herbivore‐induced changes in the plant's phenotype. The identity, order, and timing of herbivore arrivals may influence the outcome of interactions between two herbivores. How these aspects affect, in turn, subsequently arriving herbivores that feed on double herbivore‐induced plants has not been widely investigated.2. This study tested whether the order and timing of arrival of two inducing herbivores fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…SA-inducing aphids thereby reduce plant phenotypic responses to caterpillars, but the reverse effects of JA on SA are less pronounced (Zarate et al 2007, Vos et al 2013. When comparing only leaf chewers, other studies found that the first-arriving herbivore strongly determines plant resistance to other herbivores (Viswanathan et al 2007, Stam et al 2017, although subsequent herbivores have also been found to override effects of the first herbivores (Erb et al 2011, Miller-Pierce andPreisser 2012). Plant plasticity in defence against herbivores may thus be an important mediator in directing the priority effects in community assembly on an individual plant.…”
Section: Discussionmentioning
confidence: 99%
“…SA-inducing aphids thereby reduce plant phenotypic responses to caterpillars, but the reverse effects of JA on SA are less pronounced (Zarate et al 2007, Vos et al 2013. When comparing only leaf chewers, other studies found that the first-arriving herbivore strongly determines plant resistance to other herbivores (Viswanathan et al 2007, Stam et al 2017, although subsequent herbivores have also been found to override effects of the first herbivores (Erb et al 2011, Miller-Pierce andPreisser 2012). Plant plasticity in defence against herbivores may thus be an important mediator in directing the priority effects in community assembly on an individual plant.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous herbivory can induce different plant responses as compared to induction by a single herbivore (Pierre, Jansen, et al, ; Ponzio, Papazian, Albrectsen, Dicke, & Gols, ). This can have consequences for plant‐mediated interactions (Chrétien et al, ; Soler et al, ; Stam, Chrétien, Dicke, & Poelman, ; Stam et al, ) and plant seed production (Stam et al, ). Ontogenetic variation in networks of indirect plant‐mediated interactions includes these complex interactive effects on plant fitness (Poelman & Kessler, ; Rusman et al, ; Soper Gorden & Adler, ; Stam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A longer feeding period by the initial herbivore may allow more time for a plant to mount defences, which could be depleted by the time the second herbivore arrives at the plant (Karban, ; Underwood, ). In other herbivore interactions, on B. oleracea , a longer duration between feeding by P. xylostella caterpillars and B. brassicae aphids increases resistance to a third herbivore in the system, Mamestra brassicae (L.) (Stam et al., ).…”
Section: Discussionmentioning
confidence: 99%